1979
DOI: 10.1042/bj1770673
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the ferredoxin component of 25-hydroxycholecalciferol 1α-hydroxylase

Abstract: The chick kidney mitochondrial iron--sulphur protein (ferredoxin), a component of the NADPH--cytochrome P-450 reductase functional in the 1 alpha-hydroxylation of 25-hydroxycholecalciferol, was purified to homogeneity by chromatography on DEAE-cellulose, gel filtration on Sephadex G-100 and preparative electrophoresis on polyacrylamide gel. A novel NADPH--cytochrome c reductase assay utilizing crude renal NADPH--ferredoxin reductase was used for the detection of the ferredoxin. A mol. wt. of 53 000 was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Nuclease-treated rabbit reticulocyte lysate was purchased from Promega Biotech and prestained molecular-mass markers were from Integrated Separation Systems. Pansorbin cells and the detergent Nonidet P40 were obtained from Calbiochem; Autofluor autoradiography enhancer was from National Diagnostics; Kodak XAR-5 films were from Winchester X-Ray Inc. Monospecific anti-ferredoxin was obtained as reported previously [13].…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Nuclease-treated rabbit reticulocyte lysate was purchased from Promega Biotech and prestained molecular-mass markers were from Integrated Separation Systems. Pansorbin cells and the detergent Nonidet P40 were obtained from Calbiochem; Autofluor autoradiography enhancer was from National Diagnostics; Kodak XAR-5 films were from Winchester X-Ray Inc. Monospecific anti-ferredoxin was obtained as reported previously [13].…”
Section: Experimental Materialsmentioning
confidence: 99%
“…However, we could not exclude the possibility that the intense glomerular fluorescence was not a result of a reaction between the antibodies and a ferredoxin-type protein present in glomeruli which possesses biochemical functions unrelated to bioactivation of 25-OH-D3. The immunogenic similarity of beef adrenal ferredoxin (steroidogenic) to the chick renal ferredoxin despite the differences in their biochemical functions is a clear example [8]. Hence, it was essential to demonstrate that the glomerular immunofluorescence could be correlated .…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies utilizing immunofluorescent techniques [6] have shown that monospecific antibodies raised against the purified ferredoxin component of the la-hydroxylase [8] cross-react with kidney antigens predominantly localized in glomerular and proximal tubular segments of the nephron. The immunogenic reactivity in the tubular segment corroborates other reports concerning the localization of the lo~-hydroxylase in this portion of the nephron [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation